Peningkatan pengetahuan aneka olahan cabai merah besar untuk kemandirian ekonomi masyarakat - Deny Utomo; Kholid Murtadlo; Syaiful Syaiful; Cahyuni Novia (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Large red chili is one of the mainstay agricultural commodities in Karanganyar Village. Production of 85 tons of large red chili can be obtained by farmers, if there is abundant production. Every time the harvest of large red chili is not always perfect, there is often an imperfect shape of chili. Farmers usually call a large red chili reject, with a percentage of 10% (8.5 tons) each time. The price of this large red chili is cheaper than the large red chili that looks perfect. The goal to be achieved in community service activities is to increase the income of the PKK group of women through the processing of various processed large red chilies into powder, shredded rice and sauce. The method is done by using lecture and demonstration methods accompanied by training materials, and delivered directly by conducting demonstration relating to the process of making powder, shredded and sauce starting from the handling of raw materials, how to use production equipment, the process of mixing materials, cooking to packaging. The overall results of partners can make a variety of processed large red chillies and can do the packaging well.